Estrategia didáctica para desarrollo de competencias en Excel, para el cálculo de áreas y perímetros de figuras geométricas, en los estudiantes de grado 7 del colegio Universidad Antonio Nariño (2021)
This quantitative research work consisted of the development and application of a didactic strategy to strengthen skills in technology in the Excel program, through the calculation of areas and perimeters in geometric figures in students 7th grade the College at the Antonio Nariño University, a diagnosis was made, the students with the instrument "Diagnostic test on the level of apprehension in Excel" in this it was evidenced that 93% of the students had weaknesses in the skills in the use of Excel; the carrying out a theoretical analysis and an analysis of the social and cultural context of the educational institution, it is proposed to solve this problem by implementing the didactic strategy “PA-Excel,” in different pedagogical interventions to 7th grade students subsequently, the effectiveness of this strategy is evaluated by classifying it into categories using the Likert scale in the instrument "Evaluation of competences” showing that after the strategy 99% of the students managed to develop Excel competences.